Primary percutaneous coronary intervention for cardio-cerebral infarction: a case report - Watanabe, Tomomi; Kobara, Satoshi; Amisaki, Ryosuke; Yamamoto, Kazuhiro (Frontiers in Cardiovascular Medicine, 2023)
Background Acute myocardial infarction (AMI) and acute ischemic stroke (AIS) are the leading causes of death globally. Cardio-cerebral infarction (CCI) is the rare occurrence of AMI and AIS, either simultaneously or one after the other. Treatment recommendations are not clear in case of the occurrence of AMI and AIS simultaneously, especially the strategy of primary percutaneous coronary intervention (PCI). Case presentation We report consecutive seven case series of patients with CCI who underwent primary PCI in our institute. Comorbidities, strategy of primary PCI, and outcomes were investigated. All patients presented with the chief complaints associated with stroke. Atrial fibrillation (AF) was complicated in five of CCI patients, and four of AF patients were not anticoagulated. The major causes of stroke were cardiogenic and/or hemodynamic in this case series. All patients showed total occlusion in the culprit lesion, and six patients had other diseased vessels. Thrombus aspiration was mainly chosen as the reperfusion strategy in PCI. However, only two patients were diagnosed as definitive coronary embolism, and stenting was needed in six patients due to severe atherosclerotic lesion in culprit coronary artery. Final thrombolysis in myocardial infarction (TIMI) 3 flow was achieved only in four patients. Hemorrhagic complications occurred in three patients. Two patients died during in-hospital stay, and most had to be transferred for rehabilitation. Conclusions CCI was a rare but fatal condition in patients who underwent primary PCI. Although CCI was associated with concomitant atrial fibrillation, organic coronary stenosis requiring stenting for revascularization was present in almost all the cases. Given the complexity of coronary artery lesions and high in-hospital mortality, further investigations are needed to determine the optimal treatment strategy.